Urban Identity From the Perspective of Urban Atmosphere Case Study : Klungkung, Bali, Indonesia - Mahendra, Made Agus; Paturusi, Syamsul Alam; Dwijendra, Ngakan Ketut Acwin; Putra, I Dewa Gede Agung Diasana (International Journal of Engineering and Emerging Technology, 2020)
Urban areas are areas that give different atmosphere and taste in different places. There are aspects that can affect the atmosphere of urban areas. Where in each urban area has different characteristics. Klungkung city area which basically is strongly influenced by the strong cultural character of the past. Urban atmosphere has a very important role in the identity of urban areas. cities on the island of Bali have unique and unique characteristics that make the city atmosphere different. Moreover, Bali in national and international scope already has an attraction that cannot be separated from the atmosphere of the island of Bali. The atmosphere of the city space gives a different atmosphere both in the identity and character of the urban area of Klungkung, Bali. In the urban environment there is a spatial atmosphere as an indicator and reference for the development of the identity of the Klungkung urban area, Bali.    This research is motivated by the lack of understanding and understanding of the community, institutions and local governments about the atmosphere of urban space. The atmosphere of urban space provides a very important understanding and analysis of the taste and atmosphere of urban areas. The approach to the atmosphere of the city can be seen from nine aspects that must be considered in creating atmosphere in buildings and cities. The atmosphere in this study has the meaning of the sense of taste, the atmosphere in which a person is in space, creativity, taste and intention that form a shelter in a particular area. The atmosphere in this study emphasizes the atmosphere, the meaning of space and taste which includes local Balinese culture, especially in the city of Klungkung. This research uses qualitative methods by emphasizing descriptive studies, and literature studies. This study aims to determine the urban atmosphere of the Klungkung region and the relationship between the urban atmosphere and the identity of the Klungkung Bali urban area. From the results of the analysis in the conceptual order, the benefits and results obtained provide an overview of the atmosphere of the urban space as one of the identity of the Klungkung Bali urban area. Index Terms — Urban atmosphere, urban identity, urban space, urban areas